Effect of different stages on match outcomes during high level judo competitions - Ceylan, Bayram; Öztürk, Furkan; Balci, Sükrü Serdar (University of Leon, 2020)
This study aimed to demonstrate the effect of successive stages of high-level judo competitions on match outcome and the factors effecting it. A total of 4550 official matches in both men and women were included in the analysis. Frequencies and percentages were used for descriptive statistics. Mean and standard deviations with 95% confidence intervals were also presented. The difference in the variables investigated for each stage of judo competitions was analysed with the Chi-square test. Continuous variables were analysed with the Kruskal-Wallis test. The way competitors won a match differed in elimination, final stages, and medal matches (p=.02). When the difficulty of the matches increased, the percentage of the matches ended with ippon decreased and the percentage of the matches resulted with waza-ari increased. The percentage of the matches without any shido decreased from the elimination to the finals while there was a significant increase in the percentage of the matches with shido (p=.01). The match duration was found to increase from eliminations to the finals (p=.00). The efficiency index of the winner athletes during the first stage was higher than the other stages (p<.05). In conclusion, high-level judo athletes won a match with different scores at different stages during high-level judo competitions. Moreover, athletes were awarded with penalties more during the finals compared to eliminations, and match duration incrementally increased from the eliminations to the finals.
Keywords: ronda de competição índice de eficiência; Combat sports; Artes marciales asiáticas; Índice de eficiencia; Judo; match analysis; Desportos de combate; Ronda de competición; Educación Física; event phase; Análisis del rendimiento; performance analysis; judo; ronda de competición; análise de combates; análisis del rendimiento; efficiency index; artes marciales; martial arts; GV557-1198.995; Deportes de combate; índice de eficiencia; análise do rendimento; análisis de combates; artes marciais; Sports